Knowledge and perceptions on antibiotic use and resistance among high school students and teachers in New Delhi, India: A qualitative study - Kotwani, Anita (Indian J Pharmacol, 2016)
OBJECTIVE: To explore the perceptions and knowledge of school teachers and students about antibiotic use, resistance, and suggestions for practical interventions for the rational use of antibiotics. METHODOLOGY: Five focus group discussions (FGDs) with high school students (Class: 9–11) and five with teachers were conducted in two private and three public schools (one teacher and one student FGD per school) in five municipal wards of Delhi. Qualitative data on antibiotic knowledge, resistance, and behaviors with respect to antibiotics use were collected. There were 4–8 persons per teacher FGD and 15–20 persons per student FGD. FGDs were analyzed using “thematic analyses.” RESULTS: Students had poor knowledge regarding antibiotics and antibiotic resistance, while only some teachers had a basic understanding. Four broad themes needing attention emerged: definition of antibiotic and antibiotic resistance, antibiotic use behavior, doctor–patient relationship, and interventional strategies suggested to curtail the misuse of antibiotics and to spread awareness. In order to tackle these problems, both groups suggested a multipronged approach including robust public awareness campaigns also involving schools, better doctor–patient relationships, and stronger regulations. CONCLUSIONS: Although students and teachers exhibited poor knowledge about antibiotic use and resistance, they were keen to learn about these issues. School education programs and public education could be used to shape correct perceptions about antibiotic use among all stakeholders including children. This may help in the containment of antibiotic resistance and thus preservation of antibiotics for future generations.